Reverse Transcription Recombinase-Aided Amplification Assay With Lateral Flow Dipstick Assay for Rapid Detection of 2019 Novel Coronavirus - Zheng, Yu-Zhong; Chen, Jiang-Tao; Li, Jian; Wu, Xian-Jing; Wen, Jin-Zhou; Liu, Xiang-Zhi; Lin, Li-Yun; Liang, Xue-Yan; Huang, Hui-Ying; Zha, Guang-Cai; Yang, Pei-Kui; Li, Lie-Jun; et al. (Frontiers in Cellular and Infection Microbiology, 2021)
Background The emerging Coronavirus Disease-2019 (COVID-19) has challenged the global public health community. With increasing requirement of detection for SARS-CoV-2 outside of the laboratory setting, a rapid and accurate Point of Care Test (POCT) is required. Methods Targeting the nucleocapsid (N) gene of SARS-CoV-2, specific primers and probe for reverse transcription recombinase-aided amplification coupled with lateral flow dipstick (RT-RAA/LFD) platform were designed. Specificity of the RT-RAA/LFD assays was tested with human coronaviruses, human influenza A virus, influenza B viruses, respiratory syncytial virus and hepatitis B virus. Sensitivity of the RT-RAA/LFD assay was evaluated by using recombinant plasmid and SARS-CoV-2 RNA transcribed in vitro reference material. Finally, 100 clinical samples (13 positive and 87 negative for SARS-CoV-2) were tested using both quantitative reverse transcription PCR (RT-qPCR) and RT-RAA/LFD. Results The detection limit was 1 copies/μL in RT-RAA/LFD assay, which could be conducted within 30 min at 39 °C, without any cross-reactions with other human coronaviruses and clinical respiratory pathogens. Compared with RT-qPCR, the RT-RAA/LFD assay showed 100% specificity and sensitivity in the detection of clinical samples. Conclusion This work provides a convenient POCT tool for rapid screening, diagnosis and monitoring of suspected patients in SARS-CoV-2 endemic areas.